Sequence Divergence and Retrotransposon Insertion Underlie Interspecific Epigenetic Differences in Primates. (11th October 2022) - Hirata, Mayu; Ichiyanagi, Tomoko; Katoh, Hirokazu; Hashimoto, Takuma; Suzuki, Hikaru; Nitta, Hirohisa; Kawase, Masaki; Nakai, Risako; Imamura, Masanori; Ichiyanagi, Kenji
Abstract: Changes in the epigenome can affect the phenotype without the presence of changes in the genomic sequence. Given the high identity of the human and chimpanzee genome sequences, a substantial portion of their phenotypic divergence likely arises from epigenomic differences between the two species. In this study, the transcriptome and epigenome were determined for induced pluripotent stem cells (iPSCs) generated from human and chimpanzee individuals. The transcriptome and epigenomes for trimethylated histone H3 at lysine-4 (H3K4me3) and at lysine-27 (H3K27me3) showed high levels of similarity between the two species. However, there were some differences in histone modifications. Although such regions, in general, did not show significant enrichment of interspecies nucleotide variations, gains in binding motifs for pluripotency-related transcription factors, especially POU5F1 and SOX2, were frequently found in species-specific H3K4me3 regions. We also revealed that species-specific insertions of retrotransposons, including the LTR5_Hs subfamily in human and a newly identified LTR5_Pt subfamily in chimpanzee, created species-specific H3K4me3 regions associated with increased expression of nearby genes. Human iPSCs have more species-specific H3K27me3 regions, resulting in more abundant bivalent domains. Only a limited number of these species-specific H3K4me3 and H3K27me3 regions overlap with species-biased enhancers in cranial neural crest cells, suggesting that differences in the epigenetic state of developmental enhancers appear late in development. Therefore, iPSCs serve as a suitable starting material for studying evolutionary changes in epigenome dynamics during development.